Peran kecerdasan buatan dalam strategi manajemen: mengoptimalkan keputusan bisnis - Dzakirah, Nabilah Mutiara (Maliki Interdisciplinary Journal, 2025)
This journal examines the role of artificial intelligence (AI) in management strategy and optimizing business decisions. By analyzing various sources of recent literature, this research illustrates how AI has changed the business landscape, improving operational efficiency and providing competitive advantages to organizations. This study also discusses the challenges and opportunities that arise from implementing AI in the context of strategic management. The research results show that AI has a significant impact on various aspects of management, including decision making, business process optimization, digital marketing, and operational management. However, AI implementation also presents challenges such as the need for adequate infrastructure, skilled workforce, as well as ethical and data privacy issues. In conclusion, organizations that can effectively integrate AI into their management strategies will be better positioned to compete and thrive in the digital era.